Peningkatan Pemahaman dan Ketertarikan Masyarakat Arjasari terhadap Teknik Budidaya Tanaman Tomat melalui Metode NFT (Nutrient Film Technique) - Mubarok, Syariful; Fauzi, Ardika Albi; Anas, Anas; Nursuhud, Nursuhud (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2018)
The development of plant cultivation technology is now growing rapidly. One of the new technologies is thetechnology of cultivation of plants without soil or by using hydroponic system. Many types of hydroponics as we know, one ofwhich is Nutrient Film Technique (NFT). The purpose of this activity is to introduce the renewable technol ogy of tomato cultivation to the community, so that people's knowledge about the new technology of tomato cultivation will increase. Thisactivity was conducted in Arjasari Village, Arjasari, Bandung City, with the method are survey and socialization of theintroduction of tomato cultivation technology through the NFT system to the community. The results showed that prior to thesocialization of NFT, the knowledge of the community in Arjasari about NFT technology for cultivation is still low, almost70% of respondents do not know the cultivation of plants in NFT or cultivation of plants without soil. They only know thecultivation of plants on the soil. With this socialization, there has an increased of knowledge and interest of the community todo cultivation of plants in NFT. 100% of respondents showed a desire to try cultivation of plants in NFT